Vivencias emocionales de adultos mayores frente al reasentamiento en una Comunidad del Municipio de Barrancas, La Guajira.
he present research aims to identify the emotional experiences of older adults facing resettlement in a Community of the Municipality of Barrancas, La Guajira. This study has a qualitative approach, with a phenomenological design, field and cross-sectional scope. The population was composed of 29 older adults; the sample was made up of four (4) older adults. The instrument was a qualitative in-depth interview, with semi-structured, open questions. The category was emotional experiences, and the subcategories: internal and external forces, psychological tension and perception of the older adult. For the analysis of results, semantic networks were created through the atlas.ti program, where the information was coded in an orderly manner.